The effect of initial rotation in the N(2D) + H2 ? NH(3?-) + H reaction - Karabulut, Ezman; Aslan, Emine; Klos, Jacek; Bulut, Niyazi (Elsevier, 2014)
In this work, total reaction probabilities, integral cross sections and rate constants were calculated for selected initial rotational states of the H-2 molecule in the N(D-2) + H-2 reaction. Time dependent wave packet method combined with Centrifugal Sudden approximation was used and followed by a flux analysis on recently developed NH2(1(2)A '') global potential energy surface. We also investigated the effect of the projection quantum number of the initial rotational state on the reactivity. Total reaction probabilities were calculated for all values of the total angular momentum, J, in the range from 0 to 40. The effects of the initial rotational excitation of the H-2 reactant and of its projection quantum number on the behavior of rate constants were studied. The reaction rate constants are compared with previously published experimental and theoretical results. It was found that the initial rotation and its projection have a big effect on the integral cross sections. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Reaction probability; Integral cross sections; Rate constants